2016
DOI: 10.1371/journal.pone.0148451
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Reference Genes and Their Impact on Normalized Gene Expression Studies across Cultivated and Wild Cicer Species

Abstract: Quantitative Real-Time PCR (qPCR) is a preferred and reliable method for accurate quantification of gene expression to understand precise gene functions. A total of 25 candidate reference genes including traditional and new generation reference genes were selected and evaluated in a diverse set of chickpea samples. The samples used in this study included nine chickpea genotypes (Cicer spp.) comprising of cultivated and wild species, six abiotic stress treatments (drought, salinity, high vapor pressure deficit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 66 publications
9
27
0
Order By: Relevance
“…Hence, for this study, a most stable reference gene was selected on the basis of comprehensive ranking. A similar approach has also been reported in Salicornia europaea L. by Xiao et al (2015) and in chickpea (Cicer arietinum L.) by Reddy et al (2016).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Hence, for this study, a most stable reference gene was selected on the basis of comprehensive ranking. A similar approach has also been reported in Salicornia europaea L. by Xiao et al (2015) and in chickpea (Cicer arietinum L.) by Reddy et al (2016).…”
Section: Discussionsupporting
confidence: 62%
“…In the earlier studies, the CYP gene was also found to be a suitable reference gene for qRT-PCR normalization in different tissues of soybean ( Jian et al, 2008) and peanut (Reddy et al, 2013). However, this gene was not a suitable reference gene in poplar (Brunner et al, 2004), cucumber (Cucumus sativus L.; Wan et al, 2010), and chickpea (Reddy et al, 2016). Similarly, ACT 11 was also not found to be a suitable reference gene for qRT-PCR studies in different tissues of poplar (Brunner et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although ACT , GAPDH , EF , or 18s rRNA have been reported as reference genes for gene expression analysis [3032], adzuki bean is not involved in these studies. Therefore, nine genes were selected as candidate reference genes in current study and three excel-based approaches BestKeeper, geNorm and NormFinder were used to evaluate the expression stability.…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR reaction was performed using the ViiA7 Real-Time PCR System (Thermo Fisher, USA) in 384-well plates. The previously tested chickpea CaCAC gene was used as a reference gene 48 . Three replicates were included for each sample.…”
Section: Methodsmentioning
confidence: 99%